Está en la página 1de 2

# Brewsters angle derivation

## Erick Rolando Martnez Lorn

Lets start with some useful trigonometric identities. First lets review the known identity for the sine of a sum of angles: sin(a b) = sin(a) cos(b) cos(a) sin(b), Particularly if a = b sin(2a) = 2 sin(a) cos(a). We will nd very useful to write the following identities too: ) ) ) ) ) ( ( ( ( ( a+b ab a+b ab a+b ab sin(a) = sin + = sin cos + cos sin 2 2 2 2 2 2 ( ) ( ) ( ) ( ) ( ) a+b ab a+b ab a+b ab sin(b) = sin = sin cos cos sin . 2 2 2 2 2 2 Now lets add and subtract (3) and (4). We get ) ( ) a+b ab cos 2 2 ( ) ( ) a+b ab sin(a) sin(b) = 2 cos sin . 2 2 sin(a) + sin(b) = 2 sin ( (5) (6) (2) (1)

(3) (4)

We are going to use these ahead in the text. By the time, lets come back to the physics: the Brewsters angle denes the angle of incidence at which the parallel component of the reected beam rp equals zero. e Fresnel condition for this component is rp = Now lets multiply (7) by a convenient 1: [ rp = nt cos(i ) ni cos(t ) sin(t ) nt sin(t ) cos(i ) ni sin(t ) cos(t ) = . nt cos(i ) + ni cos(t ) sin(t ) nt sin(t ) cos(i ) + ni sin(t ) cos(t ) ]
ni sin(i )

## nt cos(i ) ni cos(t ) . nt cos(i ) + ni cos(t )

(7)

We can now use Snells law (ni sin i = nt sin t ) to simplify rp rp = sin(i ) cos(i ) sin(t ) cos(t ) . sin(i ) cos(i ) + sin(t ) cos(t ) (8)

Using the relation (2), we can rewrite (8) as rp = Finally, by (5) and (6), rp = We can easily rewrite (10) in terms of tangents: rp = tan(i t ) tan(i + t ) (11) cos(i + t ) sin(i t ) . sin(i + t ) cos(i t ) (10) sin(2i ) sin(2t ) . sin(2i ) + sin(2t ) (9)

Equation (11) becomes zero when the denominator tends to innity. is occurs when i + t = In terms of Snells law: ni sin i = nt sin Brewsters angle B is such that tan B = nt ni (13) ( 2 . 2 (12)

) i = nt cos i ,